Pengaruh Citra Merek Dan Kelompok Referensi Terhadap Keputusan Pembelian Smartphone Vivo - Fani Firmansyah; Adam Jarror (Jurnal Manajerial, 2021)
Background - In Indonesia, there are various smartphone brands with attractive competition because vendors continue to compete to win consumers, but one of the vendors is ranked first in the market share in 2020, namely Vivo. therefore it is necessary to know how the brand image of vivo and whether a group can influence consumer choice. Purpose - The purpose of this study was to determine the influence of brand image and reference groups on purchasing decisions of Vivo smartphones on students of the Faculty of Economics, Uin Malang. Design/ Methodology/ Approach - This type of research is quantitative. The population of this study were students of the Faculty of Economics, UIN Malang. With a sample of 90 students. The analytical method used is multiple regression, while the instrument test uses a validity test, reliability test and classical assumption test with the help of SPSS 16.0 software for windows. Result and Discussion – Testing on the brand image variable (X1), the T-count value (2.385) is greater than T table (1.987) and the significance value (0.019) is less than alpha (0.05) which indicates there is a significant positive effect on purchasing decisions (Y). Testing on the Reference Group variable, the T-count (2.167) is more than the T-table (1.987) and the significance value (0.033 is less than alpha (0.05) which indicates there is a significant positive effect on purchasing decisions (Y). Based on the test results Simultaneously, the F-count value (9.114) is greater than the F-table (3.10) and the significance value (0.000) is smaller than alpha (0.05) which indicates the influence of the brand image variable (X1) and the reference group ( X2) simultaneously has a significant positive effect on purchasing decisions (Y). Conclusion – The results of the study showed that the variable brand image and reference group simultaneously had a significant positive effect on purchasing decisions. While the partial test results that brand image has a significant positive effect on purchasing decisions and the reference group variable has a significant positive effect on purchasing decisions.